BABACAKAN SEBAGAI PRAKTIK ETNOPEDAGOGI DALAM PENCAPAIAN DIMENSI PROFIL LULUSAN DI SMP - Iis Handoko; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the potential of the babacakan tradition as a medium for ethnopedagogical practice at the junior secondary school level (SMP), particularly in supporting the achievement of the eight Dimensions of the Graduate Profile. Babacakan, as a Javanese and Sundanese cultural ritual rich in spiritual, social, and cultural meanings, contains educational values that are relevant to students’ character development. This research employed a qualitative approach with describing a fenomena at a junior secondary school in Banten that has integrated local wisdom into learning activities through the Strengthening of the Graduate Profile Dimensions program. Data were collected through in-depth interviews, participatory observation, and documentation studies. The findings reveal that babacakan embodies values that are directly correlated with the dimensions of Faith and Piety, Citizenship, Creativity, Collaboration, Independence, Health, Communication, and Critical Reasoning. The tradition also proved effective in creating contextual and meaningful learning experiences while strengthening students’ cultural identity.